Pengaruh Kondisi Sosial Ekonomi terhadap Kebrhasilan Terapi Hipertensi di RSI Kota Lamongan - Susanto Tjokro, Vanessa; Herni Suprapti (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Background: Socioeconomic status is one of the problems that people face when coming to a healthcare provider. In a developing country like Indonesia and other developing countries, socioeconomic status is strongly linked with the morbidity of a disease like hypertension, diabetes mellitus, and other generative diseases. The low level of education and household income is usually linked with the ignorance to search for a healthcare facility for their disease. Lamongan is one of the cities in East Java with about 300.000 hypertension patients. With that high number of diseases, this study aims to seek if there was any link between socioeconomic status and the success of hypertension therapy in the Islamic Hospital of Nasrul Ummah Lamongan. Methods: This study used 2 indicators to assess the socioeconomic status. They are education level (low or high) and household income (below or above Lamongan minimum regional salary). A cross-sectional design study is used in this study with a chi-square test for hypothesis Conclusion: The result from this study states that there is no link between socioeconomic status and the success of hypertension therapy.